Stabilization of peat soil by using envirotac - Norazam, Putri Nur Farah Izzati; Bakar, Ismail; Lim, Alvin John Meng Siang; Herman, Herman Shah (EDP Sciences, 2017)
Peat soil is wet and soft. It is also known as a very soft and difficult soil with high water and organic content, low shear strength, low bearing capacity and their mechanical chemical and biological properties degenerate with time. The characteristics and geotechnical properties of peat soil are mainly related to its high moisture content and high organic content respectively. This is very challenging to geotechnical engineers and construction industry as peat soil characteristic can cause excessive settlement.Soil stabilisation is the process of improving the engineering properties of the soil which will then in return make it more stable. As a result of soil stabilization, the bearing capacity and the strength of the soil will increase with an added bonus of water tightness, resistance to wash out and other properties which will also be improved. In this research, Envirotac polymer is used as the soil stabilizer which is in a form of liquid. This study is done in order to investigate the optimum mix proportion of Envirotac as a liquid stabilizer on Peat soil. The objective of this study was to determine the strength effects of 15%, 30% and 45% of Envirotec on peat sample and to investigate the shrinkage effect of stabilizing peat soil by using Envirotac. A mould sample with a diameter of 50mm and a height of 100mm was prepared. Samples were then tested after 7, 14 and 21 days. The physical properties tests conducted for this research are the Atteberg limits and moisture content test, while the mechanical test was Unconfined Compressive strength (UCS) test. The tests were carried out according to BS 1377: 1990. From the result, 30% Envirotac on peat sample has higher strength from control sample and more economical compare to use 45% Envirotac which had greater shrinkage effect